Utilization Of Palm Palm Industry Liquid Waste For Palm Oil Plantation Land Applications - Sahadi Didi Ismanto; Lisa Rahayu (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2024)
The research results show that: (1). All liquid waste requirements for land application have been fulfilled properly, even the biodegradation results in anaerobic ponds are much smaller than those required by Environmental Impact Control Agency, (2). Water quality standards in monitoring wells in gardens are based on PP No. 82 of 2001 Class II, BOD-5 and Total Nitrogen do not meet quality standards, but at the resident monitoring well location almost all parameters tested meet quality standards, COD is smaller and even oil and fat are not detected and the Total Nitrogen content is only 2.38 mg/l which has met the requirements. Waste seepage into residents' wells is not significant; (3). The results of plantations that use land applications and non-land applications are different, where the results of gardens that use liquid palm oil mill waste as land applications produce much greater fruit production (average yield is greater/ha 48.28%) than the results of oil palm plantations. (4). The use of fertilizer on land application land was initially greater than on land that did not use land application land, this was because agricultural yields had actually started to decline because they were over 20 years old, but the use of fertilizer was decreasing every year, and (5). The oil content of fresh fruit bunches (FFB) applied to garden land and non-land application shows a difference in oil content, where fresh fruit bunches (FFB) applied to garden land on average have a greater oil content than fresh fruit bunches. (TBS) non land garden application